Evaluation of Some Rheological Properties of Mixtures of Wheat Flour - Chickpea Flour by The Mixolab Device - alhammadi, wesal (Latakia University Journal -Biological Sciences Series, 2023)
The objective of this research is to study some of the chemical and rheological properties of mixtures of wheat flour with chickpea flour, according to the replacement ratios (7%, 12%, 17%, 22%, 27% and 32%), using some standards for the Mixolab device, and all analyzes were carried out in a technology laboratory. Grains, Al-Furat University. The results of estimating the protein percentage showed a significant increase with high replacement rates of chickpea flour, in addition to an increase in the average time of dough formation C1 with a significant difference from the addition ratio 12% to the ratio 32%, and the highest percentage of water absorbed at the replacement ratio was 32%, While the fall number was inversely correlated with the protein percentage. The tested mixtures with percentages (7% and 12%) can be directed towards the manufacture of biscuits, while 17% is suitable for the manufacture of baladi bread, and the replacement ratio of 27% was the best for the manufacture of ponds and ravioles.